2020
DOI: 10.3390/s21010177
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Monitoring of Yogurt Fermentation Process by Aquaphotomics Near-Infrared Spectroscopy

Abstract: Automated quality control could have a substantial economic impact on the dairy industry. At present, monitoring of yogurt production is performed by sampling for microbiological and physicochemical measurements. In this study, Near-Infrared Spectroscopy (NIRS) is proposed for non-invasive automated control of yogurt production and better understanding of lactic acid bacteria (LAB) fermentation. UHT (ultra-high temperature) sterilized milk was inoculated with Bulgarian yogurt and placed into a quartz cuvette (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 124 publications
(158 reference statements)
0
18
0
3
Order By: Relevance
“…From this point on, the differences are lower and only a slight increase in the slope is observable (orange and green spectra). The modification in baseline slope and 6900 cm −1 band are related to the overall water absorption due to the changed physical properties of the medium [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…From this point on, the differences are lower and only a slight increase in the slope is observable (orange and green spectra). The modification in baseline slope and 6900 cm −1 band are related to the overall water absorption due to the changed physical properties of the medium [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Muncan and co-authors reported that the entire wavelength region of 1300-1400 nm has significant importance during the aquaphotomics analysis of the fermentation of milk with lactic acid bacteria. According to these authors, this region corresponds to the absorbance of weakly or non-hydrogen-bonded water, indicating the existence of a protein concentrate in liquid phase, in other words, non-coagulated protein [59]. The hydrolysis of proteins by trypsin, prior to fermentation, facilitates the breakdown of exogenous proteins into lower molecular-weight oligopeptides, which increases the solubility of proteins and reduces the coagulation of proteins [60].…”
Section: Aquaphotomics Analysismentioning
confidence: 99%
“…This feature has been already used to track changes induced by cheese ripening [16], to screen water's quality in the presence of certain contaminants [17], to elucidate yoghurt fermentation mechanisms [18], to authenticate honey [19], and many more applications [20][21][22][23]. With regards to coffee analysis, this approach could prove particularly beneficial in case of the shortage of beans, the absence of technically qualified coffee quality assessors as well as the insufficiency of the chemicals used for other sophisticated methods.…”
Section: Introductionmentioning
confidence: 99%